2020
DOI: 10.1007/s00423-020-02019-2
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Petersen’s defect in gastrectomy for gastric cancer: an interrupted time series analysis from a high-volume institution in China

Abstract: Purpose Petersen’s hernia (PH) is a serious complication after gastrectomy for gastric cancer. The aim of this study was to investigate whether closure of Petersen’s defect (PD) can decrease the rates of PH and suspected Petersen’s hernia (SPH). Methods Patients who underwent gastrectomy with PD were enrolled. From January 2014 to January 2017, we performed gastrectomy without PD closure (non-closure group). From February 2017 to June 2018, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In recent years, a series of studies has demonstrated that closure of Petersen space or mesenteric defect could significantly reduce the risk of internal hernia ( 13 , 15 , 16 ). Therefore, it has been recommended as a routine step during gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a series of studies has demonstrated that closure of Petersen space or mesenteric defect could significantly reduce the risk of internal hernia ( 13 , 15 , 16 ). Therefore, it has been recommended as a routine step during gastrectomy.…”
Section: Discussionmentioning
confidence: 99%